It gets better with age: Resilience, stigma, and mental health among lesbian, gay, bisexual, transgender and queer persons from Poland - Koziara, Karolina; Mijas, Magdalena E.; Galbarczyk, Andrzej; Wycisk, Jowita; Pliczko, Mateusz P.; Krzych-Miłkowska, Karolina; Grabski, Bartosz (Frontiers in Psychology, 2022)
Lesbian, gay, bisexual, transgender and queer populations are disproportionately affected by chronic stress associated with stigma which contribute to health adversities including depression. Negative impact of stigma on health can be alleviated by factors such as resilience. Little is known however on how exposure to stigma, protective factors and mental health change with age among gender and sexually diverse persons. Our study aimed at investigating this issue. Our sample consisted of (i) 245 sexually diverse cisgender women, (ii) 175 sexually diverse cisgender men and (iii) 98 transgender and gender diverse persons. We collected data through a web-based survey. Linear regression models were performed to investigate the interactions of age and each group of participants for resilience, stigma exposure, and mental health indicators (depression and self-esteem). The analysis yielded no significant relationships between stigma exposure and age in distinguished groups. However, we observed significant interaction effects of distinguished groups of participants and age in case of self-esteem, depression, and resilience. Self-esteem and resilience were related positively, and depression was negatively associated with age in all study groups. Additionally, we observed that sexually diverse cisgender men demonstrated significantly increased resilience, reduced depression and higher self-esteem compared to other groups. Although the exposure to stigma did not decrease with age, resilience and self-esteem increased, suggesting that LGBTQ persons manage to thrive despite adversities.